Cold-Water Immersion Has No Effect on Muscle Stiffness After Exercise-Induced Muscle Damage - Pinto, João (2019)
Objective: To analyze the effect of cryotherapy on muscle stiffness after exercise-induced muscle damage. Design: A leg-to-leg comparison model. Setting: University research laboratory. Participants: Thirty (30) untrained men (21.1 ± 1.6 years, 177.6 ± 6.4 cm, 75.9 ± 10.0 kg, and 15.9 ± 2.9% fat mass) with no history of lower-limb injury and no experience in resistance training. Intervention: All participants underwent a plyometric exercise program to induce muscle damage; however, randomly, one leg was assigned to a treatment condition and subjected twice to cold-water immersion of the lower limb at 10°C (±1°C) for 10 minutes, while the other leg was assigned to control. Main Outcomes Measures: Longitudinal stiffness and passive transverse stiffness were evaluated on the soleus and gastrocnemius muscles at 4 moments: pre-exercise, immediately after exercise, 24 hours, and 72 hours after the damage protocol. Furthermore, pressure pain threshold (PPT) and maximal voluntary isometric contraction (MVIC) were also assessed in the same periods. Results: No significant differences between control and cryotherapy were observed in regard to MVIC (P = 0.529), passive longitudinal stiffness (P = 0.315), and passive transverse stiffness (P = 0.218). Only a significant decrease was observed in PPT on the soleus muscle in the cryotherapy compared with the control leg immediately after exercise (P = 0.040). Conclusions: The results show that cryotherapy had no influence on muscle stiffness. However, cryotherapy had a positive effect on PPT immediately after exercise.